2017
DOI: 10.1093/hmg/ddx409
|View full text |Cite
|
Sign up to set email alerts
|

Aminoglycoside-mediated promotion of translation readthrough occurs through a non-stochastic mechanism that competes with translation termination

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Aminoglycoside antibiotics have long been suggested as a way to promote PTC recognition by near cognate tRNA, essentially competing with translation termination [ 49 ] and enabling the synthesis of a full-length protein [ 50 , 51 ]. Despite initial concerns with toxicity and side effects, these molecules have shown some success in clinical trials.…”
Section: Suppression Of Nonsense Mutations: Approaches and Challenmentioning
confidence: 99%
“…Aminoglycoside antibiotics have long been suggested as a way to promote PTC recognition by near cognate tRNA, essentially competing with translation termination [ 49 ] and enabling the synthesis of a full-length protein [ 50 , 51 ]. Despite initial concerns with toxicity and side effects, these molecules have shown some success in clinical trials.…”
Section: Suppression Of Nonsense Mutations: Approaches and Challenmentioning
confidence: 99%
“…Amlexanox, Ataluren, RTC13 and G418 have proven to be effective in read-through induction in several different PTCs both in vitro and in vivo (Gonzalez-Hilarion et al, 2012;Howard et al, 1996;Heier and DiDonato, 2009;Floquet et al, 2011;Salvatori et al, 2009;Brasell et al, 2019;Yu et al, 2014;Tan et al, 2011;Wilschanski et al, 2011;Du et al, 2008;Sánchez-Alcudia et al, 2012;Schwarz et al, 2015;Martorell et al, 2019). However, it is also important to mention that some criticism has been raised against Ataluren, its mode of action and its ability to induce PTC read-through (Chowdhury et al, 2018;McElroy et al, 2013;Auld et al, 2009;Dranchak et al, 2011). Adequate dosage and incubation time may be factors for each of the tested compounds, but our choice of both relied on past published readthrough induction in various in vitro/vivo conditions (Gonzalez-Hilarion et al, 2012;Lentini et al, 2014;Heier and DiDonato, 2009;Tan et al, 2011;Sánchez-Alcudia et al, 2012;Dranchak et al, 2011;Gómez-Grau et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This process is driven by a quartenary complex consisting of a specialised selenocysteine tRNAsec, a specific elongation factor, a specific RNA secondary structure named SECIS, and GTP. Interestingly, aminoglycosides have been proposed to promote also SECIS-mediated translation [166]. X-ray crystallography and single-molecule FRET analysis revealed that several aminoglycosides such as G418 and gentamicin can directly interact with the 80S eukaryotic ribosome at multiple sites in the large and small subunits.…”
Section: Aminoglycoside Compoundsmentioning
confidence: 99%